Penetrating Neck Injury to the Superior Thoracic Artery Managed by Video-Assisted Thoracoscopic Surgery. (7th February 2013) - Wong, Victor W.; Gordy, Stephanie D.; Schreiber, Martin; Tieu, Brandon H.
Abstract : Penetrating trauma to the axillary artery and its branches is uncommon and associated with high morbidity and mortality. Open exploration is mandated in hemodynamically unstable patients, but surgical exposure can be difficult due to the concentration of vital structures and complex anatomy in this region. Computed tomographic angiography is a potential diagnostic modality in hemodynamically stable patients. In these patients, endovascular therapies may provide a feasible means of controlling hemorrhage while minimizing surgical complications. A high incidence of concomitant intrathoracic injury has resulted in an expanding role for video-assisted thoracoscopic surgery. In this paper, we present a case of penetrating injury to the superior thoracic artery that was not amenable to endovascular therapy and was ultimately managed with thoracoscopic surgery.